Pengaruh Konsep Diri Terhadap Komunikasi Interpersonal Pada Mahasiswa - Novia, Stefani; Roswiyani, Roswiyani (Peneliti.net, 2023)
Interpersonal communication is the interaction of two or more people that generates feedback. There are still many students who do not have interpersonal communication skills. One of the factors that influence interpersonal communication is the self-concept. The self-concept is an individual view of himself. A negative self-concept can cause individuals to withdraw from social relationships. It affects interpersonal communication. This research aims to determine the effect of self-concept on students' interpersonal communication. The participants in the study consisted of 204 students in Jakarta aged 18-25 years. The measurement used in this study is the Tennessee Self Concept Scale and the interpersonal communication scale. Data fetching using purposive sampling with a type of quantitative research. The analysis technique used is simple linear regression analysis using SPSS. This research indicates that self-concept affects the student's interpersonal communication by 37,1%. Research shows a significant positive relationship between self-concepts and students' interpersonal communication, so it's concluded that a more positive self-concept of students will increase their interpersonal communication capabilities.